A Novel Control Method for Integer Orders Chaos Systems via Fractional-Order Derivative - Ping Zhou; Fei Kuang (Discrete Dynamics in Nature and Society)
A fractional-order control method is obtained to stabilize the point in chaos attractor of integer orders chaos systems. The control law has simple structure and is designed easily. Two examples are also given to illustrate the effectiveness of the theoretical result.